2021
DOI: 10.1088/1361-6595/abff72
|View full text |Cite
|
Sign up to set email alerts
|

Reducing energy cost of in situ nitrogen fixation in water using an arc-DBD combination

Abstract: In this study, a sustainable air plasma-based nitrogen fixation into reactive nitrogen species in water (e.g. nitrate and nitrite) is presented, which mimics the lightning-based nitrogen fixation that occurs in nature. We report a hybrid plasma system that combines a dielectric barrier discharge (DBD) reactor (as an efficient ozone source) and an arc plasma reactor (as an efficient NO x source). This hybrid plasma system completely converts gaseous NO x and O 3 into NO −x in water with almost zero emissions (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…In addition, even at these conditions, NO 2 − can be effectively transferred to NO 3 − , introducing an additional oxidation step in the production chain as, for instance, done elsewhere. 53…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, even at these conditions, NO 2 − can be effectively transferred to NO 3 − , introducing an additional oxidation step in the production chain as, for instance, done elsewhere. 53…”
Section: Resultsmentioning
confidence: 99%
“…In addition, even at these conditions, NO 2 − can be effectively transferred to NO 3 − , introducing an additional oxidation step in the production chain as, for instance, done elsewhere. 53 In summary, the liquid phase analysis has shown that a significant portion of the N-containing species generated in the plasma indeed dissolve in the liquid phase forming mainly NO 2…”
Section: Liquid Phase Analysismentioning
confidence: 96%
“…28,40 Using the energy consumption of 8 MJ mol −1 reported, 28 generating 0.0016 mol rN in water would require ∼59,000 MJ ha −1 annually. In more realistic fertigation scenarios, fertilizer can be periodically generated at a high rate, such as the generation rate of 0.11 mol L −1 during 5 min reported in Dinh et al, 28 and then stored and distributed in its aqueous form when power is not readily available. 21 The company Nitricity utilized an ARPA system in order to fertigate 18.6 m 2 of tomato crops and was able to supply fertilizer at a maximum annual rate of 224 kg N ha −1 , 55 demonstrating the feasibility of ARPA systems to be used on the commercial scale.…”
Section: H N 2nhmentioning
confidence: 99%
“…Therefore, atmospheric pressure plasma has better application prospects in gas catalytic conversion but the energy cost needs to be further reduced to about 0.7 MJ mol −1 to be a highly competitive alternative. [23] So far, a variety of atmospheric pressure plasma sources, such as gliding arc (GA) discharge, [15,16,[24][25][26][27][28][29][30][31][32] microwave (MW) discharge, [33,34] dielectric barrier discharge (DBD), [36,37] spark discharge, [38] glow discharge, [38,39] and so on, have been developed and used in gas catalytic conversion. In addition, the nitrogen fixation effect and energy cost of these plasma sources have also been evaluating by many researchers.…”
Section: Introductionmentioning
confidence: 99%